CASE STUDY OF THE ESTABLISHMENT OF MAINTENANCE MECHANISM OF INJECTION MACHINE - Lin, Chin-Chiuan; Shih, Yen-Wen (Graduate Program of Universitas Tarumanagara, 2023)
Maintaining the normal operation of machinery and equipment in order to reduce the failure rate and increase the utilization rate is one of the most important tasks of on-site management. This research is mainly based on the establishment of relevant equipment inspection and maintenance specifications, the establishment of tables, and the promotion to on-site practical explanation, operation drills, and introduction and implementation. And use the DMAIC process of Six-Sigma to verify the improvement process. Before the equipment maintenance mechanism is introduced, the utilization rate, downtime, and number of failures were about 64.9%, 1603 min/month, and 16.7 times/month, respectively. After about half year implementation of the maintenance mechanism, its utilization rate, downtime, and number of failures were 76.13%, 250 min/month, and 3.5 times/month, respectively. Which has a significant improvement. Furthermore, in terms of tangible aspects, there are obvious improvements in increasing the utilization rate, reducing the number of failures, shortening the downtime, reduce manpower need, and raw material consumption. In the intangible aspect, the operator thus feels the cleanliness of the equipment is improved, the normal operation to reduce workload, and the work in a happy mood.